2009
DOI: 10.1002/mame.200800251
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between the Shape of Viscosity Functions and the Molecular Structure of Long‐Chain Branched Polyethylenes

Abstract: The viscosity functions of long‐chain branched metallocene‐catalyzed ethene homopolymers and copolymers (LCB‐mPE) were described by an extended Carreau‐Yasuda model. The two characteristic relaxation times, λ1 and λ2, and the slope of the viscosity function between these two characteristic relaxation times can be correlated to the zero shear‐rate viscosity, η0, and the molar mass $\overline M _{\rm w} $. The characteristic relaxation times, λ1 and λ2 (describing the main curvatures of the viscosity function) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 48 publications
4
31
0
1
Order By: Relevance
“…Stadler and Münstedt [88,315] sought to use size-exclusion chromatography with multiangle laser light scattering (SEC-MALLS), and shear rheological measurements to analyze viscosity functions of LCB polyethylenes, by separating the influence of long-chain branching and molecular weight on rheology. Doerpinghaus and Baird [316] parameterized the pom-pom model, which describes the nonlinear rheology of BPs semiquantitatively [53,163,165,166,[317][318][319][320], to shear and extensional rheology for different levels of LCB.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stadler and Münstedt [88,315] sought to use size-exclusion chromatography with multiangle laser light scattering (SEC-MALLS), and shear rheological measurements to analyze viscosity functions of LCB polyethylenes, by separating the influence of long-chain branching and molecular weight on rheology. Doerpinghaus and Baird [316] parameterized the pom-pom model, which describes the nonlinear rheology of BPs semiquantitatively [53,163,165,166,[317][318][319][320], to shear and extensional rheology for different levels of LCB.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…They found rheology to be more sensitive to branching, as expected, but reported that a combination of both the methods resulted in better overall characterization. Some of the works previously referenced also employ multidetector methods [88,219,220,302,315].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Various shear viscosity functions for metallocene-catalyzed long-chain branched PEs were also reported. [96,113,114] An extended Carreau-Yasuda model, Equation (26), was introduced by Münstedt group [113] to describe the viscosity function of distinct metallocene-catalyzed PEs with long-chain branches…”
Section: Zero Shear Viscosity η 0 and Shear Thinning Behaviormentioning
confidence: 99%
“…All measurements were performed in the linear viscoelastic regime on a TA Instruments AR-G2 or ARES in nitrogen atmosphere. An in-depth description of the experimental methods for the rheological measurements is given elsewhere (Stadler and Münstedt 2009;Stadler et al 2006b). …”
Section: Methodsmentioning
confidence: 99%